Community willingness to participate in prehospital injury care: A cross-sectional survey of injury-prone areas along the national 3 highway in Cameroon - Elvis Asangbeng Tanue; Casey Chun; Alan Hubbard; OConnor Kathleen; Odette D. Kibu; Serge Ngekeng; Nicholas Tendongfor; Nahyeni Bassah; Sandra I. McCoy; Rasheedat Oke; Isaac Obeng-Gyasi; Georges Nguefack-Tsague; et al. (PLoS ONE, 2025)
Background Road traffic injuries (RTIs) are a growing public health problem requiring urgent attention in Cameroon where emergency medical services (EMS) are underdeveloped. In other countries, training laypersons to provide prehospital care has been shown to improve injury outcomes, but requires buy-in from the persons being trained to provide care. To inform development of a lay first responder (LFR) program in Cameroon, this study aimed to assess the willingness of community members and associated factors to provide prehospital care for RTIs along the N3 highway, a road linking Cameroon’s two largest cities, known to have high incidence of RTIs. Methods We conducted a cross-sectional survey of community members living along the N3 highway, between June 18th and August 16th, 2024. Health district officials and community leaders identified N3 communities across 11 health districts with high rates of RTI. Purposeful sampling was performed in each community to assess exposure to injury and willingness to participate in prehospital care. Trained research assistants verbally administered a structured questionnaire to each consenting household representative; data collected included socio-demographic characteristics, injury exposure, first aid knowledge and attitudes, and willingness to provide prehospital care to victims of RTIs. Associations between demographic factors and willingness to provide prehospital care were assessed using multivariable logistic regression. Data were analyzed using IBM-SPSS version 26.0 and statistical significance was set at p < 0.05. Results A total of 449 adult community members were surveyed. Most [268 (59.7%)) respondents were male with a median age of 33 years (interquartile range: 26–40). The majority, 333 (74.6%) community members were willing to provide care to injured victims. However, a third [167 (37.2%)] had adequate knowledge (scored ≥ 80%) of first aid and only 23 (5%) had been trained in first aid. Factors independently associated with willingness to provide prehospital care included having adequate first aid knowledge (adjusted odd ratio (aOR) = 1.69, 95% confidence interval (CI): 1.01–2.81, p = 0.046), primary education (aOR=4.20, 95% CI: 1.19–4.81, p = 0.026) and secondary education (aOR=4.70, 95% CI: 1.34–16.53, p = 0.016) compared to respondents with no formal education, prior witness of RTI (aOR=1.68, 95% CI: 1.055–2.68, p = 0.028), being aged between 30 and 40 years (aOR=1.82, 95% CI: 1.06–3.14, p = 0.031) and community members being able to call dedicated phone numbers to report RTIs (aOR=3.11, 95% CI: 1.28–7.54, p = 0.012). Conclusion Most community members living in injury exposed-communities reported willingness to participate in prehospital care. However, first-aid knowledge is currently lacking in these communities. LFR training is needed in these communities to enable willing community members to contribute to prehospital efforts for RTIs along this road network.